ART OF TEXTILE DESIGN AMONG TRIPURI COMMUNITY OF BURATALI VILLAGE IN SOUTH TRIPURA: A REFERENCE - Acharya, Sri Apu; Bhowmik, Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The art of weaving textile has been explored to find out the uniqueness and their values of various design and motifs in fabric art of every tribal community. It finds the culture, belief and aesthetic values, which represents the beauty of art in different motifs and designs in their textiles. A particular motif has also relation with the color, shape and values which make an arrangement to compose a design. A motif is also a part of design which can be made in different shape such as geometrical, graphical, natural and floral, etc. The term composition is regularly used in visual arts to construct a form. The artisan of Tripuri community places the form in their own way. Like others, the artisan of Tripuri community of Tripura, weave various designs on their traditional attires, the women of this community are following their indigenous techniques and methods. During the field study, it has been found that the design which has been introduced in their clothes and costumes which reflect their rich culture and heritage. The artisan of Tripuri community is introduced variety of design and symbols in the edge of resha and pasra weaving is a process, which passed down from one generation to the next in tribal community. In addition, it is pre-requisite for every tribal girl to know how to weave, otherwise she would not be considered eligible as a bride. In this paper, the significance of motifs and design which are being used in Tripuri textile will be the main part of exercise and the construction of loom and the stages of looms are also been described which represent the dignity of the culture of this community.